1999
DOI: 10.1002/(sici)1097-0215(19990531)81:5<761::aid-ijc16>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gelatinase A (MMP-2) by batimastat and captopril reduces tumor growth and lung metastases in mice bearing Lewis lung carcinoma

Abstract: We have examined the effects of the synthetic matrix metalloproteinase inhibitor, batimastat (BB‐94) and the angiotensin‐converting enzyme inhibitor, captopril, on metalloproteinase activity of murine Lewis‐lung‐carcinoma cells (3LL) in vitro, and on local growth and lung metastasis of the same tumor implanted intramuscularly in syngeneic C57BL/6 mice. The effect of BB‐94 and captopril on the survival of the 3LL‐tumor‐bearing mice was also examined. Here we report that captopril treatment resulted in decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 16 publications
(24 reference statements)
3
61
0
4
Order By: Relevance
“…Neither the injections of bestatin and captopril nor bestatin in combination with captopril influenced the number of lung tumour colonies. 39 According to Prontera et al, 40 the effect of the synthetic MMP-2 inhibitor batimastat and captopril resulted in 51 and 80% inhibition, respectively, of tumour growth and metastases. Captopril pretreatment augmented the antitumour action of cyclophosphamide, expressed in terms of the survival time and the number of cured mice.…”
Section: Lung Carcinomamentioning
confidence: 99%
“…Neither the injections of bestatin and captopril nor bestatin in combination with captopril influenced the number of lung tumour colonies. 39 According to Prontera et al, 40 the effect of the synthetic MMP-2 inhibitor batimastat and captopril resulted in 51 and 80% inhibition, respectively, of tumour growth and metastases. Captopril pretreatment augmented the antitumour action of cyclophosphamide, expressed in terms of the survival time and the number of cured mice.…”
Section: Lung Carcinomamentioning
confidence: 99%
“…Epidemiological studies suggest that the incidence of cancer and cancer deaths are lower in hypertensive patients taking ACE inhibitors than in those treated with other classes of antihypertensives (Lever et al, 1998). Captopril has been shown to inhibit matrix metalloproteases 2 and 9, which are involved in the angiogenic process (Prontera et al, 1999).…”
mentioning
confidence: 99%
“…The rationale for the combination of captopril and the matrix metalloprotease inhibitor (MMPI) marimastat in this study comes from pre-clinical studies using the murine Lewis lung carcinoma model (Prontera et al, 1999). When captopril was administered with the MMPI Batimastat, the combination had synergistic activity both in inhibition of matrix metalloproteases 2 and 9 in the tumour cells and in blocking tumour growth and metastasis.…”
mentioning
confidence: 99%
“…To prevent these activities in a disease setting, interference with the activity of MMPs has been proposed as a therapeutic strategy. Synthetic low molecular weight inhibitors of these enzymes, therefore, have been tested in model systems and, in a number of studies, a clear inhibition of tumor growth was reported, [2][3][4][5][6] thus providing support for the clinical use of such inhibitors. However, in contrast, some studies demonstrated that inhibition of MMP activity had no effect or even led to an augmentation of the tumor.…”
mentioning
confidence: 99%